Comparative phylogeography reveals cryptic diversity and repeated patterns of cladogenesis for amphibians and reptiles in northwestern Ecuador - Arteaga Navarro, Alejandro Federico (2015)
Comparative phylogeography is now a common approach to understand how historical processes have shaped the formation of lineages in a broad spectrum of codistributed populations of different taxa. However, these types of studies are scarce in the Neotropics, a region that is characterized by speciose assemblages, complex geological history, and poorly understood historical biogeography. To cope with this lack of knowledge, in this study, we apply a broad comparative approach to investigate the diversification patterns, if any, of five lineages of amphibians and reptiles codistributed at the biogeographic boundaries of the Choco and Andes ecoregions in northwester Ecuador. Mitochondrial sequences were used to determine the degree of diversification within species. Our results highlight congruent patterns of parapatric speciation and common geographical barriers for distantly related taxa. These comparisons indicate similar biological and demographic characteristics for the included clades, and reveal the existence of two new species of Pristimantis previously subsumed under P. walkeri. Our data supports the hypothesis that widely distributed Chocoan taxa may generally experience their greatest opportunities for isolation and parapatric speciation across elevational thermal gradients in the adjacent montane forests. Finally, our study provides critical information to predict which unstudied lineages may harbor cryptic diversity, and how geology and climate are likely to have shaped their evolutionary history.